2022
DOI: 10.1002/adma.202110155
|View full text |Cite
|
Sign up to set email alerts
|

Polymerized Small Molecular Acceptor with Branched Side Chains for All Polymer Solar Cells with Efficiency over 16.7%

Abstract: The power conversion efficiencies (PCEs) of small molecule acceptor (SMA)‐based organic solar cells have already exceeded 18%. However, the development of polymer acceptors still lags far behind their SMA counterparts mainly due to the lack of efficient polymer acceptors. Herein, a series of polymer acceptors named PY‐X (with X being the branched alkyl chain) are designed and synthesized by employing the same central core with the SMA L8‐BO but with different branched alkyl chains on the pyrrole motif. It is f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
61
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 99 publications
(68 citation statements)
references
References 51 publications
1
61
0
Order By: Relevance
“…16–19 The recent success of Y-series SMAs has accelerated the development of PSMAs and a few representative PSMAs with PCEs over 16% have been reported. 20–22 In the pioneering attempts of molecular optimization, much effort has been focused on the modifications of the SMA main building block, 23 fluorinated end group, and π-bridge. 24–26 Besides these approaches, the random copolymerization comprising three or more functional units in the backbone which can integrate the complementary advantages of each chromophore appears to be a very promising and feasible synthetic strategy for fine-tuning the optical and electronic properties of polymer acceptors.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…16–19 The recent success of Y-series SMAs has accelerated the development of PSMAs and a few representative PSMAs with PCEs over 16% have been reported. 20–22 In the pioneering attempts of molecular optimization, much effort has been focused on the modifications of the SMA main building block, 23 fluorinated end group, and π-bridge. 24–26 Besides these approaches, the random copolymerization comprising three or more functional units in the backbone which can integrate the complementary advantages of each chromophore appears to be a very promising and feasible synthetic strategy for fine-tuning the optical and electronic properties of polymer acceptors.…”
Section: Introductionmentioning
confidence: 99%
“…In our recent work, we reported an efficient polymer acceptor named PY-DT by modifying the beta position of the thiophene unit core with branched alkyl chains. 22 It was shown that the branched alkyl chain modification of SMA-DT could lead to upshifted lowest unoccupied molecular orbital (LUMO) energy levels and blue-shifted absorption spectra, and thereby an improved open-circuit voltage ( V oc ) of 0.949 V in the related photovoltaic device. Nevertheless, because of the blue-shifted absorption, the short-circuit current density ( J sc ) of the PY-DT-based all-PSC is limited to 23.40 mA cm −2 .…”
Section: Introductionmentioning
confidence: 99%
“…Both higher short-circuit current density (J sc ) and fill factor (FF) values are responsible for a higher PCE for PBDTBT HH . Several solvent additives were also tested for further device optimization [60,61]. The addition of 2 vol% 1-chloronaphthalene (CN) resulted in clearly improved photovoltaic performance.…”
Section: Photovoltaic Propertiesmentioning
confidence: 99%
“…31–33 In recent years, the new types of polymerized small molecular acceptors endow the polymer–polymer device with a rapid increase in PCE. 34–48 However, this type of all-polymer blend exhibits a poorer stability due to the low molecular weight. Accordingly, material designs based on current, mature, efficient all-polymer systems aiming to promote the stability of the morphology should be a meaningful strategy.…”
Section: Introductionmentioning
confidence: 99%